Interfacial magnetic anisotropy in Py/MoS2 bilayer - Jamilpanah, Loghman; Hajiali, Mohammadreza; Mohseni, Seyed Majid (Journal of magnetism and magnetic materials, 2020)
•The anisotropic magnetoresistance (AMR) in permalloy (NiFe, Py)/MoS2 bilayers is systematically studied.•A strong enhancement of AMR by the MoS2 layer is observed.•The AMR enhancement cannot be due to presence of the spin Hall magnetoresistance.•The enhanced AMR in the Py/MoS2 bilayers can be attributed to the interfacial hybridization at the interface. The anisotropic magnetoresistance (AMR) in permalloy (NiFe, Py)/MoS2 bilayer is studied and a strong enhancement of AMR in Py layer is observed due to the MoS2 coating on its surface. The spin Hall magnetoresistance and the induced magnetic moment by interfacial magnetic proximity effect at the Py/MoS2 interface cannot explain the observed AMR enhancement. In order to find the origin of the observed MR increase in Py/MoS2 sample, the magnitude of magnetic anisotropy constants are derived from torque curves on the basis of AMR data. The enhanced AMR in the Py/MoS2 bilayers can be attributed to the interfacial hybridization at the interface. Our findings enrich the understanding of the magnetoresistance of metallic FM/transition metal dichalcogenide (TMDC) bilayers and present AMR enhancement for application in spintronic devices.